Variability of urban surface temperatures and implications for aerodynamic energy exchange in unstable conditions. (16th October 2018) - Crawford, Ben; Grimmond, Sue B.; Gabey, Andrew; Marconcini, Mattia; Ward, Helen C.; Kent, Christoph W.
Abstract : Sensible heat flux ( Q H ) is a critical driver of surface and boundary layer meteorological processes, especially in urban areas. Aerodynamic resistance methods (ARM) for modelling Q H are promising because, in principle, all that is needed is surface temperature ( T 0 ), air temperature ( T A ) and an aerodynamic resistance term ( r H ). There are significant challenges in urban areas, however, due to uncertainties in satellite‐derived land surface temperatures ( LST ), logistical challenges in obtaining high‐resolution air temperatures, and a limited understanding of spatial and temporal variability of r H and associated variables (e.g. thermal roughness length). This work uses an extensive LST dataset covering 6 years (2011–2016) in central London and a long‐term in situ observation network to analyse the variability of LST and r H variables. Results show that LST is spatially correlated with building and vegetation land cover with coherent thermal structures at length scales less than 500–1, 000 m. Additionally, satellite‐observed LST varies with average building height (up to 10% cooler in areas with tall buildings). The r H term and associated variables are observed to vary on daily and seasonal cycles, and findings are used to model Q H using five variations of an ARM‐based approach on a 100 m pixel basis. Modelled Q H is compared to observations from three scintillometer paths and an eddy covariance flux tower. We find generally good agreement between observations and models, although there is uncertainty in all methods (mean absolute error ranges from 58.1–129.3 W/m 2 ) due to the challenges involved in determining high‐resolution meteorological and surface inputs, particularly LST and friction velocity ( u * ). Additional complexity in evaluating modelled Q H arises from anthropogenic heat sources: long‐term tower‐based observations show that T A and the radiometer‐derived T 0 are warmer during working weekdays than non‐working days (up to 0.7 °C) and that there is an observed lag (2–3 hr) between energy consumption and the observed warming and modelled Q H . Abstract : Surface temperatures and heat emissions are critical drivers of meteorology in urban areas, but there is limited understanding of surface‐based energy exchange processes in cities. This work uses satellite‐observed surface temperatures to develop high‐resolution sensible heat flux models. Surface temperatures and heat exchange show coherent spatial structures and vary with land cover and building height. Important meteorological and anthropogenic variables controlling energy exchange are observed to vary seasonally and diurnally. Models are evaluated using a unique in situ observation network.